A Self‐Healing Aqueous Lithium‐Ion Battery. (12th October 2016) - Zhao, Yang; Zhang, Ye; Sun, Hao; Dong, Xiaoli; Cao, Jingyu; Wang, Lie; Xu, Yifan; Ren, Jing; Hwang, Yunil; Son, In Hyuk; Huang, Xianliang; Wang, Yonggang; et al.
Abstract: Flexible lithium‐ion batteries are critical for the next‐generation electronics. However, during the practical application, they may break under deformations such as twisting and cutting, causing their failure to work or even serious safety problems. A new family of all‐solid‐state and flexible aqueous lithium ion batteries that can self‐heal after breaking has been created by designing aligned carbon nanotube sheets loaded with LiMn2 O4 and LiTi2 (PO4 )3 nanoparticles on a self‐healing polymer substrate as electrodes, and a new kind of lithium sulfate/sodium carboxymethylcellulose serves as both gel electrolyte and separator. The specific capacity, rate capability, and cycling performance can be well maintained after repeated cutting and self‐healing. These self‐healing batteries are demonstrated to be promising for wearable devices.